Hydrogen production from biogas: Process optimization using ASPEN Plus®. (30th December 2022) - Phan, Thanh Son; Pham Minh, Doan; Espitalier, Fabienne; Nzihou, Ange; Grouset, Didier
Abstract: This work is part of the VABHYOGAZ (valorization of biogas into hydrogen) program, which targeted the industrial deployment of hydrogen production from biogas in France. To-date, different processes of methane reforming, such as steam reforming of methane (SRM), dry reforming of methane (DRM) and tri-reforming of methane (TRM), have been studied in the literature, but only SRM is applied at industrial scale. Since SRM is an energy-intensive process, a critical analysis of these routes for hydrogen production from biogas is indispensable for process optimization. This has been addressed in this work, by using ASPEN Plus® simulation. Different global processes of hydrogen production from biogas, via DRM, SRM, or TRM, with or without tail gas recycling, have been studied. Among them, hydrogen production using TRM technique (H2 -TRM0.3C process) with a partial recycling of tail gas (30%) was found to be the best option, leading to the highest hydrogen production rate and the best energy yield. H2 -TRM0.3C process was also found to be more efficient than the actual industrial process (H2 -REF), which is based on SRM technique. Under the same conditions, H2 -TRM0.3C process led to a higher H2 production (8.7% more), a lower total energy consumption (18.6% less), and a lower waste heat generation (15.4% less), in comparison with the actual industrial process (H2 -REF). Graphical abstract: Image 1 Highlights: H2 production from biogas are simulated using ASPEN Plus® software. DRM with or without tail gas recycling: less competitive than SRM. TRM without tail gas recycling: less competitive than SRM. TRM with tail gas recycling: the best option with the highest H2 yield.